EFL bachelor’s students’ experiences in writing recount texts through daily english journaling: a focus on advantages and obstacles - Anggi Handayani Harahap; Ahmad Amin Dalimunthe; Ernita Daulay (SCHOULID: Indonesian Journal of School Counseling, 2025)
This study investigates the experiences of sixth-semester EFL undergraduate students at UIN Sumatera Utara in implementing daily English journaling to develop their writing skills. Specifically, it aims to (1) explore students’ engagement with journaling as a tool for writing development, (2) identify the perceived benefits of this practice, and (3) examine the challenges they face during the process. Using a qualitative approach with a phenomenological case study design, the research involved five purposively selected participants over a six-week period of daily journaling. Data were collected through semi-structured interviews, journal samples (comprising 30 entries per participant), reflective logs, and field notes. The data were analyzed using Miles, Huberman, and Saldaña’s interactive model, involving data condensation, display, and conclusion drawing. Trustworthiness was ensured through prolonged engagement, triangulation, member checking, and persistent observation. The findings indicate that sustained journaling over time fostered writing fluency—evidenced by increased word count per entry, greater lexical variation, and reduced grammatical errors. Participants also reported enhanced confidence, improved sentence structure, and greater awareness of their writing habits. Nevertheless, challenges such as limited vocabulary, inconsistent motivation, lack of feedback, and time constraints were frequently noted. These results underscore the pedagogical value of journaling as a reflective, low-stakes writing practice in EFL contexts. The study offers practical insights for educators on integrating journaling into writing instruction and highlights the need for guided feedback mechanisms to optimize learning outcomes.